O universo de Clara Crocodilo : história & música no LP de Arrigo Barnabé - Batista, Juliana Wendpap (2013)
This work aims to analyzes the LP Clara Crocodilo, Arrigo Barnabé (1980). The LP, which marked the called Vanguard Paulista, brings tales to music with serial techniques, chronicling the daily lives of lonely and insecure urban characters. The work is evaluated on his creative process, considering the trajectory of Arrigo Barnabé and the historical context of development of the eight compositions that make up this album. This study is a dialogue between history and music. The analysis includes poetic and musical texts in search of connections to the contingent of social change in Brazil between 1970 and 1980 decades.